2022
DOI: 10.1002/wene.467
|View full text |Cite
|
Sign up to set email alerts
|

A review of phase change materials and heat enhancement methodologies

Abstract: Phase change materials (PCMs) are an efficient alternative to store and release heat at a specific range of temperature. Here PCMs and heat enhancement methodologies for PCM storage are reviewed. A short overview of PCMs and their applications is presented in addition to the progress during the last 10 years. Heat enhancement techniques, that is, extended surfaces, multiple and composite PCMs, and encapsulation techniques, are presented along with a statistical overview of studies during 2016-2021. The importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 161 publications
0
6
0
Order By: Relevance
“…The shell‐and‐tube type of LHTES is the most oftenused configuration as of its benefits, such as simple design, low cost, low‐pressure drop, large heat transfer area, high discharge power, and high efficiency 49 . Furthermore, the PCM will be placed between the two tubes, which directly exchange heat between the heat transfer fluid (HTF) and the working fluid, as proposed by several researchers 50–52 . Aside from that, the industry uses shells and tubes 90% of the time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shell‐and‐tube type of LHTES is the most oftenused configuration as of its benefits, such as simple design, low cost, low‐pressure drop, large heat transfer area, high discharge power, and high efficiency 49 . Furthermore, the PCM will be placed between the two tubes, which directly exchange heat between the heat transfer fluid (HTF) and the working fluid, as proposed by several researchers 50–52 . Aside from that, the industry uses shells and tubes 90% of the time.…”
Section: Methodsmentioning
confidence: 99%
“…49 Furthermore, the PCM will be placed between the two tubes, which directly exchange heat between the heat transfer fluid (HTF) and the working fluid, as proposed by several researchers. [50][51][52] Aside from that, the industry uses shells and tubes 90% of the time. It comprises a shell, a tube, baffles, a front head, a rear head, and a nozzle.…”
mentioning
confidence: 99%
“…PCMs are substances capable of conducting reversible phase transitions between solid and liquid states while absorbing or releasing thermal energy within a small temperature variation. This unique property makes them invaluable in various applications such as passive heating and cooling systems, building thermal management, and photo-to-thermal conversion. Within various PCMs, poly­(ethylene glycols) (PEGs) possess the advantages of high phase change enthalpy and thermal reliability, suitable phase change temperature, nontoxicity, and low cost . However, pure PEGs as well as other pure PCMs usually exhibit intrinsically poor photo-to-thermal conversion ability.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, porous supports serve to confine PCMs within nanopores, preventing potential leakage in liquid form through the capillary and surface tension forces . Various porous supports, including SiO 2 , polymers, carbonaceous materials, metal foams, and aerogels, are commonly employed for confining PCMs. Among these options, SiO 2 is widely favored for its tunable porous structure, high thermal stability, wide availability, and nontoxic nature . Furthermore, SiO 2 has demonstrated the capability to adsorb substantial amounts of PCMs, reaching up to 70–80%, thereby offering high thermal energy storage capacity for resulting SSPCMs. , Notably, the SiO 2 prepared by Li et al achieved stabilization of up to 97% PEG, marking the highest PCM loading level reported.…”
Section: Introductionmentioning
confidence: 99%